Enhancing Students’ Participation in Learning Vocabulary Through Scrabble Game - Roma, Kholifuddin (YASIN, 2025)
This study focused on the learning activity in the classroom learning vocabulary to enhance students’ participation through the scrabble game. It was classroom action research. The research subject was SMP Negeri 4 Singkawang, especially the seventh-grade students of VII G class. The data was collected with tools, an observation checklist and field notes. The data was analyzed through Miles and Huberman's interactive data analysis techniques. The result showed that in the first cycle, several students were not actively involved in the learning process. However, in the second cycle, learning vocabulary through the scrabble game could enhance the students’ participation because they had fun, motivated, and engaging learning while playing.